INVESTIGATION OF FOULING EFFECT ON OVERALL PERFORMANCE OF SHELL AND TUBE HEAT EXCHANGER IN A UREA FERTILIZER PRODUCTION COMPANY IN NIGERIA (Nigerian Journal of Technology, 2015)
Fouling is one of the major problems confronting heat exchangers in most industries. Shell and tube heat exchangers are perhaps the most common types of heat exchangers in industrial applications due to their flexibility and versatility. This study investigated the effect of fouling on the performance of the shell and tube heat exchanger unit of a CO2 fertilizer production company in Nigeria. Two different heat exchanger units (cold gas pre-heater and CO2 water cooler in scrubbing process) were considered for the analysis of this study. Data were obtained from operational log book, periodic maintenance data sheet and vendor’ design data sheet. The data were analyzed using various energy equations encoded in MATLAB to determine the overall heat transfer coefficients, heat duties, capacity ratios and effectiveness. The results obtained from the analysis showed that on average, the deviation of overall heat transfer coefficient, heat duty, and effectiveness from design values were 24.10%, 26.27%, and 17.17% respectively. Fouling factor was 31.58% more than the design value in a period of 47 days of operation. Fouling adversely affects the performance parameters of the heat exchangers. http://dx.doi.org/10.4314/njt.v35i1.20